Acute Ischemic Pancreatitis Following Cardiac Arrest: A Case Report - Piton, Gaël; Barbot, Olivier; Manzon, Cyril; Moronval, Frederic; Patry, Cyrille; Navellou, Jean-Christophe; Belle, Evelyne; Capellier, Gilles (JOP. Journal of the Pancreas, 2010)
Context Ischemia is an established cause of acute pancreatitis; however, acute pancreatitis has never been reported after cardiac arrest. Case report We report a case of acute pancreatitis following cardiac arrest with prolonged cardiopulmonary resuscitation in a 58-year-old man, the mechanism of which is likely to be ischemic. The patient developed severe ischemic encephalopathy, leading to death. Possible causes of acute pancreatitis in a context of cardiopulmonary resuscitation are discussed. Conclusion In case of abdominal distension following cardiac arrest, diagnoses of mesenteric ischemia and acute ischemic pancreatitis should be considered. Such digestive complications occurring after cardiac arrest probably reflect the severity of the ischemia. Image: Increased abdominal volume observed in the first hours following cardiac arrest.